The Managed Body Developing Girls and Menstrual Health in the Global South - Bobel, Chris; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
The Managed Body is an invested critique of the discourses of 'Menstrual Hygiene Management' (MHM)--a growing social movement to support menstruating girls in low and middle income countries. Bobel shows how MHM organizations frame the issues by claiming menstruating girls encounter 'a hygienic crisis' that authorizes rescue. Faced by the challenges of capturing attention and directing resources, MHM advocates often inadvertently rely upon weak evidence and spectacularized representations to promote a product-centered, consumerist agenda that actually accommodates more than it resists the core problem of menstrual stigma.
Chapter 1: Introduction: What a Girl Needs... -- Part I: Context -- Chapter 2: The Girling of Development -- Chapter 3: Making Menstruation Matter in the Global South: Mapping a Critical History of the Menstrual Hygiene Management Movement -- Part II: Framing the Problem: Stories of Risk, Risk of Stories -- Chapter 4: "Can You Imagine?" Making the Case for a Bloody Crisis -- Chapter 5: The Spectacle of the 'Third World Girl' and the Politics of Rescue -- Part III.Framing the Solution: Developing the 'Good Body' -- Chapter 6: "Dignity Can't Wait": Building a Bridge to Human Rights -- Chapter 7: Disciplining Girls through the Technological Fix: Modernity, Markets, Materials -- Chapter 8: Beyond the Managed Body: Putting Menstrual Literacy at the Center -- Appendix A: Methods -- Appendix B: Notes on Language.
Keywords: Sex; Medical anthropology; Social medicine; Economic development; Gender Studies; Medical Anthropology; Medical Sociology; Development Studies